Gadopentetate Dimeglumine as a Contrast Agent in Common Carotid Arteriography - Erly, William K.; Zaetta, Julie; Borders, Guy T.; Ozgur, Hasan; Gabaeff, Dina R.; Carmody, Raymond F.; Seeger, Joachim (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Despite improvements in noninvasive imaging, some patients with contraindications to iodine-based contrast material still require angiography for the evaluation of carotid stenosis. Our aim was to assess the utility of gadopentetate dimeglumine as an intraarterial contrast agent in common carotid angiography.METHODS: Twelve patients with suspected carotid artery stenosis were enrolled in the study. In addition to the standard injection sequences with iohexol, common carotid arteriograms were obtained after administration of gadopentetate dimeglumine. Neurologic status and vital signs were monitored during and for 6 hours after the examination. For each injection, five independent observers, blinded to the contrast agent used, measured the percentage of carotid stenosis and assessed their confidence in grading the stenosis, the overall quality of the examination, and, in cases of decreased quality, the reason(s) for it. Statistical analysis was done with paired and unpaired t-tests with equal variances.RESULTS: No patient had an adverse clinical outcome, and measurements of carotid artery stenosis showed no statistically significant differences between the gadopentetate dimeglumine and iohexol examinations. Overall image quality and observer confidence in measurements of stenosis on the gadolinium-based studies were slightly but significantly lower than those of identical iodine-based studies.CONCLUSION: Gadopentetate dimeglumine may be an alternative to iodine in selected patients undergoing carotid angiography. Although overall image quality of the gadolinium studies is slightly inferior to that of the iohexol studies, measurements of carotid artery stenosis are similar for the two examinations.